Automatic intensity windowing of mammographic images based on a perceptual metric. Issue 4 (22nd March 2017) - Albiol, Alberto; Corbi, Alberto; Albiol, Francisco
Abstract : Purpose: Initial auto‐adjustment of the window level WL and width WW applied to mammographic images. The proposed intensity windowing (IW) method is based on the maximization of the mutual information (MI) between a perceptual decomposition of the original 12‐bit sources and their screen displayed 8‐bit version. Besides zoom, color inversion and panning operations, IW is the most commonly performed task in daily screening and has a direct impact on diagnosis and the time involved in the process. Methods: The authors present a human visual system and perception‐based algorithm named GRAIL (Gabor‐relying adjustment of image levels). GRAIL initially measures a mammogram's quality based on the MI between the original instance and its Gabor‐filtered derivations. From this point on, the algorithm performs an automatic intensity windowing process that outputs the WL/WW that best displays each mammogram for screening. GRAIL starts with the default, high contrast, wide dynamic range 12‐bit data, and then maximizes the graphical information presented in ordinary 8‐bit displays. Tests have been carried out with several mammogram databases. They comprise correlations and an ANOVA analysis with the manual IW levels established by a group of radiologists. A complete MATLAB implementation of GRAIL is available athttps://github.com/TheAnswerIsFortyTwo/GRAIL . Results: Auto‐leveled images show superior quality both perceptually and objectively compared to their full intensity range and compared to the application of other common methods like global contrast stretching (GCS). The correlations between the human determined intensity values and the ones estimated by our method surpass that of GCS. The ANOVA analysis with the upper intensity thresholds also reveals a similar outcome. GRAIL has also proven to specially perform better with images that contain micro‐calcifications and/or foreign X‐ray‐opaque elements and with healthy BI‐RADS A‐type mammograms. It can also speed up the initial screening time by a mean of 4.5 s per image. Conclusions: A novel methodology is introduced that enables a quality‐driven balancing of the WL/WW of mammographic images. This correction seeks the representation that maximizes the amount of graphical information contained in each image. The presented technique can contribute to the diagnosis and the overall efficiency of the breast screening session by suggesting, at the beginning, an optimal and customized windowing setting for each mammogram.